PROBLEM OF CLIMATIC CHANGES IN THE CZECH REPUBLIC MINING AREA - Schmidt, Pavel; Rehor, Michal (International Multidisciplinary Scientific GeoConference SGEM, 2020)
If we compare the deviations of the average ground temperatures in 1991 - 2008 from the average in 1961 - 1990, we find that southern Europe is warming relatively the slowest (the average linear trend of temperature increase recalculated for decades is 0,43 °C), more central Europe (0,48 °C) and the fastest changes occur in the northern part of the continent (0,67 °C) - with increasing latitude, the temperature increase in Europe increases. The two main climatological characteristics that are most subject to the ongoing changes in the Earth's climate system and about which we have the most information - temperature and precipitation - can serve as basic indicators of climate change. Due to the uncertainties of the outputs of global climate models and methods of regional downscaling, the outputs of regional models for the territory of the Czech Republic are burdened with a higher degree of uncertainty than the outputs of models for the territory of the European continent, resp. the whole planet. According to RCP 4.5, the warming will occur by about 2,0 °C at the end of the century, and according to RCP 8.5 to 4,1 °C. For the territory of the Czech Republic, the following graphic outputs were processed for the parameters of the average annual temperature.